Antiviral Properties of the NSAID Drug Naproxen Targeting the Nucleoprotein of SARS-CoV-2 Coronavirus - Terrier, Olivier; Dilly, Sébastien; Pizzorno, Andrés; Chalupska, Dominika; Humpolickova, Jana; Bouřa, Evžen; Berenbaum, Francis; Quideau, Stéphane; Lina, Bruno; Fève, Bruno; Adnet, Frédéric; Sabbah, Michèle; et al. (Molecules (Basel, Switzerland), 2021)
There is an urgent need for specific antiviral treatments directed against SARS-CoV-2 to prevent the most severe forms of COVID-19. By drug repurposing, affordable therapeutics could be supplied worldwide in the present pandemic context. Targeting the nucleoprotein N of the SARS-CoV-2 coronavirus could be a strategy to impede viral replication and possibly other essential functions associated with viral N. The antiviral properties of naproxen, a non-steroidal anti-inflammatory drug (NSAID) that was previously demonstrated to be active against Influenza A virus, were evaluated against SARS-CoV-2. Intrinsic fluorescence spectroscopy, fluorescence anisotropy, and dynamic light scattering assays demonstrated naproxen binding to the nucleoprotein of SARS-Cov-2 as predicted by molecular modeling. Naproxen impeded recombinant N oligomerization and inhibited viral replication in infected cells. In VeroE6 cells and reconstituted human primary respiratory epithelium models of SARS-CoV-2 infection, naproxen specifically inhibited viral replication and protected the bronchial epithelia against SARS-CoV-2-induced damage. No inhibition of viral replication was observed with paracetamol or the COX-2 inhibitor celecoxib. Thus, among the NSAID tested, only naproxen combined antiviral and anti-inflammatory properties. Naproxen addition to the standard of care could be beneficial in a clinical setting, as tested in an ongoing clinical study.
Keywords: nucleoprotein; Chlorocebus aethiops; influenza; drug repurposing; Humans; Nucleoproteins; přehodnocení terapeutických indikací léčivého přípravku; simulace molekulového dockingu; Viral Proteins; Drug Repositioning; Vero buňky; Molecular Docking Simulation; inflammation; lidé; zvířata; Anti-Inflammatory Agents, Non-Steroidal; antiflogistika nesteroidní; Virus Replication; buněčné linie; Cercopithecus aethiops; virové proteiny; Cell Line; antivirové látky; structure-based drug design; replikace viru; farmakoterapie COVID-19; Antiviral Agents; antiviral; oligomerization; Animals; SARS-CoV-2; naproxen; nukleoproteiny; Naproxen; COVID-19 Drug Treatment; Vero Cells